Applying emotion to high school band performance - Mahr, Erin (Kansas State University, 2019)
In my lesson, students learned ways to connect emotionally with their audience through shared experience. In Aaron Perrine’s work, Tears of St. Lawrence, Perrine’s inspiration for his work was watching a meteor shower with his young daughter. After listening to and reflecting on music my students felt a connection to, they discovered that using dynamics and rubato will help add emotion and audience connection to their music. I have developed more as a teacher in this program by putting more thought into my teaching philosophy, and the contemplating the reasons I enjoy teaching daily, supported by the ideas of the philosophers I studied. When learning about these philosophers, I found that I strongly align with David Elliot’s teachings and promote the idea that all students can be creative music makers with the encouragement from their teacher to explore improvisation, composing, and arranging. I encourage my concert band students to discover improvisation in our warm up time by modeling a musical pattern of their creation and having the band echo that same pattern back. In learning about Elliot Eisner, it helped me realize that even if some of my students will not continue with music after high school, their time in my class performing music will give them a source of pleasure and encourage higher thinking skills. By learning about specific music education philosophy, I know what my short term and long term goals are with my students and how I want them to grow as a result of participating in my classes during their time in high school. My overall knowledge as a band director has improved during my time in this program. I enjoyed learning about the history and development of wind band literature and about repertoire I was not familiar with as a musician. Another development of my teaching has been the organization skills learned in my classes. I found new ways to prioritize paperwork and have a thorough band handbook to cover policies and expectations as well as useful information on instrument brands and accessories and recommended private teachers. I also organized my marching band task list into a monthly task list so that I do not feel overwhelmed at any one point in the year.
Keywords: Student improvisation; Emotion in music; High school band; Audience connection